2001
DOI: 10.1038/sj.ejhg.5200741
|View full text |Cite
|
Sign up to set email alerts
|

Low incidence of UPD in spontaneous abortions beyond the 5th gestational week

Abstract: Approximately 15 ± 20% of all clinically recognised pregnancies abort, most commonly between 8 ± 12 gestational weeks. While the majority of early pregnancy losses is attributed to cytogenetic abnormalities, the aetiology of approximately 40% of early abortions remains unclear. To determine additional factors causing spontaneous abortions we retrospectively searched for uniparental disomies (UPD) in 77 cytogenetically normal diploid spontaneous abortions. In all cases an unbalanced chromosome anomaly was ruled… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0
3

Year Published

2002
2002
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(25 citation statements)
references
References 39 publications
0
22
0
3
Order By: Relevance
“…However, UPD also causes abnormal embryonic/fetal development or even miscarriage, although the frequency of UPD-associated miscarriage may be low, which was estimated to occur in < 3% of miscarriage cases. 21,22 Several studies found that UPDs, for example, with maternal uniparentalheterodisomy of chromosome 9, 21 paternal UPD of chromosome 14, 22 maternal uniparentalisodisomy and uniparentalheterodisomy of chromosome 16, 23 and paternal uniparentalisodisomy of chromosome 21, 21 could cause miscarriage. Moreover, it was well known that wholegenome UPD was not compatible with life, and paternal origin would lead to complete hydatidiform mole, resulting in embryonic death.…”
Section: Discussionmentioning
confidence: 98%
“…However, UPD also causes abnormal embryonic/fetal development or even miscarriage, although the frequency of UPD-associated miscarriage may be low, which was estimated to occur in < 3% of miscarriage cases. 21,22 Several studies found that UPDs, for example, with maternal uniparentalheterodisomy of chromosome 9, 21 paternal UPD of chromosome 14, 22 maternal uniparentalisodisomy and uniparentalheterodisomy of chromosome 16, 23 and paternal uniparentalisodisomy of chromosome 21, 21 could cause miscarriage. Moreover, it was well known that wholegenome UPD was not compatible with life, and paternal origin would lead to complete hydatidiform mole, resulting in embryonic death.…”
Section: Discussionmentioning
confidence: 98%
“…In the literature to date, only three cases of UPDs 9, 16, and 21 have been found among spontaneous abortions (Fritz et al 2001;Kondo et al 2004), and the present case is the first report of UPD 14 in a spontaneous abortion. In other reports, the association of UPDs with spontaneous abortions has not been found (Shaffer et al 1998;Smith et al 1998).…”
Section: Discussionmentioning
confidence: 84%
“…To date, few UPD cases have been found among spontaneous abortions (Fritz et al 2001;Kondo et al 2004). To investigate the involvement of UPDs, we analyzed the chromosomal origin of spontaneous abortions in detail using microsatellite polymorphic markers and found UPD of chromosome 14 and a unique exchange of chromosome 7 in cases of spontaneous abortion.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, our study was underpowered to estimate the actual incidence of correction events in the clinical PGS population. However, our data are well matched with a retrospective search for UPD in 77 cytogenetically normal diploid spontaneous abortions, indicating that 2.5% of genetically unexplained miscarriages were associated with whole chromosome UPD (Fritz et al, 2001). We thus look forward to see additional data from blastocyst stage PGS cycles using higher resolution chromosomal screening tests.…”
mentioning
confidence: 82%